Design of hybrid PV-wind stand-alone renewable energy system: Case study. Issue 1 (2nd January 2018) - Fulzele, Jyoti B.; Daigawane, Manoj B.; Daigawane, Prema M.
Abstract: A systematic designed hybrid renewable energy system play an important role for the development of cost effective, highly reliable and continuity of energy supply in the rural areas. This paper presents the case study of Dhudhgaon village for the design of hybrid PV-Wind stand alone system. For simulation purpose, hourly electrical load profile, monthly solar radiation, monthly wind speed data and technical specification of all components has been generated and used as input data. The main objective of this study has to minimize total net present cost of the system also check the technical capability of system using other parameters like capacity shortage, renewable fraction, COE and excess energy. The well-known freeware HOMER research tool have been used for simulation and optimization of hybrid PV-Wind system.